Effectiveness of the “pain-free dental injection” (PaFein) teaching model in reducing children’s pain: A randomized, controlled study. - BEKİROĞLU, GÜLNAZ NURAL (My University, 2022)
Purpose: This study explores the effectiveness of a comprehensive structured teaching model – the “PaFein” – for instructing postgraduate pediatric dental residents in the provision of pain-free local anesthesia to children. Methods: Ten postgraduate pediatric dental residents and 172 children between the ages 5 and 13 participated in the study following ethical approval. The previously measured baselines guided the randomization of study and control groups. The study group (five residents) attended the PaFein course (9 hours). Based on power calculations, residents performed dental injections (8 mandibular block, 8 palatal/lingual and 14 buccal infiltrations) in randomly assigned child patients. Demographic data of residents/children, parental and self-report anxiety scores and Visual Analogue Scale (VAS) pain scores were noted to examine children’s anxiety and pain during dental injections. Results: Children’s mean anxiety score did not differ significantly between groups; however, VAS pain reports during dental injections (a, b, c, d) were found lower in the PaFein study group than the control group (p < 0.05). VAS pain reports for (a) buccal injections were 1.08 and 1.9 (p = 0.02); (b) inferior alveolar nerve blocks were 1.58 and 3.37 (p = 0.0002); (c) palatal/lingual injections were 1.34 and 3.02 (p < 0.0001); (d) total means were 1.28 and 2.59, respectively (p = 0.0001). VAS pain reports of anxious and non-anxious children in the PaFein study group (1.63 and 1.17) were also lower than the control group (3.33 and 2.39) (p < 0.0001 and p = 0.005). Conclusion: The “PaFein” teaching model was found to be effective in training dental residents to reduce dental injection pain in children, including the anxious ones.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Medicine; Dentistry; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Klinik Tıp (MED); Klinik Tıp; TIBBİ BİLİŞİM; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICAL INFORMATICS; DENTISTRY, ORAL SURGERY & MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Tıbbi Bilişim; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Health Informatics; Family Practice; Medicine (miscellaneous); General Medicine; anxiety; dental anesthesia; education; pain; pediatric dentistry